Prawo do rzetelnego procesu w postępowaniu arbitrażowym w sprawach sportowych na gruncie standardów Europejskiej konwencji praw człowieka - Kopczyk, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
Taking into account the fast growing number of cases concerning sports issues, the author tries to show problematic aspects related to arbitration proceedings in sports affairs in light of the European Convention on Human Rights provisions. The author focuses on matters related to athlete’s right to a fair trial. Having that in mind, the analysis of selected rules this right comprises of was conducted: the right of access to an independent and impartial Tribunal and presumption of innocence principle. The article ends with a conclusion, which also contains findings resulting from the aforementioned analysis.
Keywords: Europejska Konwencja Praw Człowieka; prawo do rzetelnego procesu; rzetelny proces; postępowanie arbitrażowe